PERBEDAAN MOTIVASI KERJA BERDASARKAN SHIFT KERJA KARYAWAN PT. SAKTI PANGAN PERKASA - Glory Anatasya Makikama; Yari Dwikurnaningsih; Sapto Irawan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research aims to know the significance of differences in work motivation based on employee work shift of PT. Sakti Pangan Perkasa. Type of this research is comparative-research. The variables in this research are work motivation and employee work shift. Population in this research are 63 employees. The sampling technique uses total sampling, so the research sample is employee of PT. Sakti Pangan Perkasa as much 63 as employees. Data collection techniques in each instrument using a Likert scale. The analysis technique used One Way ANOVA technique and using the help of IBM Statistics SPSS 20. The result of the analysis show that the Fhitung is 5.890 and the signicance value of F is 0,005. Based on these results it can be concluded that there are differences in work motivation based on employee work shift of PT. Sakti Pangan Perkasa Karanganyar. The suggestion that the author proposes to the next researcher is to conduct further research by adding variables